The effect of foreign direct investment, total trade and external debt on the economic growth of Malaysia / Muhammad Kamil Abdul Rahman - Abdul Rahman, Muhammad Kamil (Faculty of Business and Management, 2007)
The objective of this study is to see the relationship and effects between the inflow of foreign direct investment and economic growth, the relationship and effects between total trade and economic growth, and the relationship and effects between external debt and economic growth in Malaysia. The data consists of quarterly data of inflow of foreign direct investment, total trade and external debt from 1997 to 2006. The methods used are Pearson Correlation Matrix, Durbin -Watson statistic, Standard Error or Mean Square, F-value, Coefficient of Variable, R Square or Coefficient of Determination to examine the relationship between the inflow of foreign direct investment, total trade and external debt on the economic growth of Malaysia. The data has been interpreted and analyze by using Statistical Package for Social Science. From the findings and analysis I am able to identify the relationship between the variables. Hopefully, from the findings of this research can give some benefits to fellow students, the business faculty of UiTM and everybody in Malaysia including the government and they will use it for further reference. The results show that there is a negative relationship between inflow of foreign direct investment on the economic growth of Malaysia, and also a positive relationship between total trade and external debt on the economic growth of Malaysia.